Os sentidos do aprisionamento na contemporaneidade : um estudo de caso no Presídio do Serrotão em Campina Grande-PB - César Segundo, Breno Wanderley (2011)
This thesis aims to discuss, in a historic perspective, processes of prisons constitution, the main changes in which they have been through and how such a trajectory reflects in Brazilian society, with the objective of a better understanding the historic senses and current disputes. Before Brazilian prison model, we present a case of study at Serrotão Prison, in Campina Grande, Paraíba state, northeast of Brazil. We intend to research about new senses imposed by the general dynamics of capitalism to prisons and about how these questions of macro nature reflect a concrete situation in the local. Taking approaches on development and constitution of prisons in western societies, by Foucault, Bauman, Wacquant, Michel Cavadino, James Digman and others, we search to understand which current senses are in dispute contemporarily. This work was built through bibliography research, documents research, interviews and a focal group, besides direct observation. We indicate how the State lost its mission on socializing prisoners and created the organized crime phenomenon, particularly in the interior of prisons as a response for lack of sense for prisons as a space of social recovering. We search to present senses currently attributed to Brazilian prison system, for prisoners, prisons administrators and institutions in this sector, proving that the State does not accomplish its role of socializing prisoners and showing that, the lack of public policies towards them when they leave prison make them keep returning to prison.